2018
DOI: 10.3390/app8071200
|View full text |Cite
|
Sign up to set email alerts
|

An Ergonomic Customized-Tool Handle Design for Precision Tools using Additive Manufacturing: A Case Study

Abstract: A study was carried out with 135 surgeons to obtain a surgical laparoscopic grasper handle design that adapts to the size of each surgeon's hand, in a functionally appropriate way, and has the sufficient ergonomics to avoid generating the problems detected nowadays. The main conclusion of the work is the practical 3D parametric design obtained for a laparoscopic surgical graspers handle that is scalable to fit each particular surgeon's hand size. In addition, it has been possible to determine that the anthropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Other studies also indicated that axial handles require significantly more muscle activity than the other common types of instrument handle [37]. In this study, we have analyzed the relationship between the surgeons' ergonomics and performance and different sizes of a novel laparoscopic instrument handle design [11]. The results verify that the use of different instrument handle sizes has consequences on the surgeon's grip pressure and surgical skills.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Other studies also indicated that axial handles require significantly more muscle activity than the other common types of instrument handle [37]. In this study, we have analyzed the relationship between the surgeons' ergonomics and performance and different sizes of a novel laparoscopic instrument handle design [11]. The results verify that the use of different instrument handle sizes has consequences on the surgeon's grip pressure and surgical skills.…”
Section: Discussionmentioning
confidence: 56%
“…All participants performed the tasks using the new design of the instrument handle with their dominant hand and a conventional laparoscopic instrument with their non-dominant hand. Four participants were novice Additionally, the parametric 3D CAD design allowed us to easily scale the model to fit different hand sizes in an ergonomic way using the Palm Length Measured (PLM) [11]. Therefore, four different sizes (XS, S, M and L) ( Figure 2) were 3D printed for this study following the specifications defined in previous studies [10,11].…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of ergonomic criterions also in equipment manufacturing, as well as in material handling activities, could minimize the impact of WMSDs [15, 16].…”
Section: Discussionmentioning
confidence: 99%